Research on B2B business model of operators in 5G era - Xiaoxia WANG; Hui ZHAO; Yufei CUI; Kun LI; Xiao WANG (Dianxin kexue)
B2B business model in 5G era will become the main competition area for operators.Opportunities come along with challenges from investment,market and technology such as huge construction expenditure,fragmented market and difficulties of industry integration.Research on B2B operation cases of domestic and foreign operators and internet giants in the post 4G and 5G era had been done,from which “communication +” service model,industry coordinator model and platform model were investigated especially.Finally,three B2B operations models of domestic operators were proposed.